Carbon Absorption Potential on Seagrass Types Enhalus acoroides and Thalassia hemprichii In Morotai Island Water - Nurafni; Iswandi Wahab; Balgis Bachmid; Rinto M. Nur; Kismanto Koroy; Djainudin Alwi; Titien Sofiati; Any Kurniawati (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Seagrass is one of the most important ecosystems in coastal areas. Seagrass beds can absorb carbon of 1.15 tons/ha, with a carbon content below the substrate of 0.88 tons/ha (76.3%), higher than the carbon above the substrate, which is only 0.27 tons/ha (23, 7%). Research on carbon absorption in seagrass is still relatively carried out, so it is necessary to research the potential for carbon absorption in seagrass types Enhalus acoroides and Thalassia hemprichii in Morotai waters. The research will be carried out from September to December 2021, starting with seagrass sampling in three sub-districts (South Morotai, East Morotai, and South West Morotai Districts). The types of seagrass used were Enhalus acoroides and Thalassia hemprichii. Biomass sample analysis was carried out at the Basic Laboratory of the Faculty of Fisheries and Marine Sciences, Pacific Morotai University. Carbon analysis on seagrass was carried out at the Chemical Oceanography Laboratory of the Faculty of Marine and Fisheries Sciences, Hasanudin University Makassar. The seagrass sampling method used the quadratic transect method and sample analysis using the method Loss On Ignition (LOI). The results showed that Thalassia hemprichii has the highest carbon content in the roots, with a value of 38.94 gC/m2 to 49.48 gC/m2. In contrast, Enhalus acoroides has the highest carbon content in the roots with a carbon value of 30.77 gC/m2 to 37.86 gC/m2.